Students' Perceptions of Social Competence of Guidance and Counseling Teachers - Muslima, Muslima (Global Education Journal, 2025)
Each individual's perspective will provide different meanings that are influenced by the individual's own condition. This study aims to determine how students perceive the social competence of BK teachers at SMP Negeri 4 Banda Aceh and what efforts are made to develop the social competence of BK teachers at SMP Negeri 4 Banda Aceh. The method used in this study is descriptive qualitative, while the data collection technique used in this study is the interview technique. The subjects of the study were 1 BK teacher and 6 students of SMP Negeri 4 Banda Aceh consisting of class VIII and class IX. The results of the study showed that students' perceptions of the social competence of BK teachers in terms of attitude, communication, socializing with students, fellow educators, parents and the community are good, this can be seen from the attitude of BK teachers who are positive, firm, have a pleasant personality, are friendly and are able to establish good cooperation with educators,  parents and other communities. Efforts that can be made by BK teachers in developing their social competence are by maximizing the provision of services even though they are constrained by the limited time given at school, namely by developing creative service programs online (online) such as creating online services by utilizing technology such as zoom, WA, and so on.